Key Science Goals for the Next-Generation Event Horizon Telescope - Michael D. Johnson; Kazunori Akiyama; Lindy Blackburn; Katherine L. Bouman; Avery E. Broderick; Vitor Cardoso; Rob P. Fender; Christian M. Fromm; Peter Galison; José L. Gómez; Daryl Haggard; Matthew L. Lister; et al. (Galaxies, 2023)
The Event Horizon Telescope (EHT) has led to the first images of a supermassive black hole, revealing the central compact objects in the elliptical galaxy M87 and the Milky Way. Proposed upgrades to this array through the next-generation EHT (ngEHT) program would sharply improve the angular resolution, dynamic range, and temporal coverage of the existing EHT observations. These improvements will uniquely enable a wealth of transformative new discoveries related to black hole science, extending from event-horizon-scale studies of strong gravity to studies of explosive transients to the cosmological growth and influence of supermassive black holes. Here, we present the key science goals for the ngEHT and their associated instrument requirements, both of which have been formulated through a multi-year international effort involving hundreds of scientists worldwide.